2022
DOI: 10.1088/1755-1315/1059/1/012021
|View full text |Cite
|
Sign up to set email alerts
|

The effects of biochar-compost on soil properties and plant growth performance grown in a sandy-loam soil

Abstract: Sandy soils properties with low nutrients availability and high porosity could be improved with the combination application of biochar-compost to increase the plant productivity. The objective of this study was to examine the impacts of different rates compost-biochar addition on sandy-loam soil properties and cabbage (Brassica chinensis L. var. parachinesis) growth performance. The oil palm empty fruit bunch biochar was pyrolyzed at temperature ranging between 450 to 500°C. Different rates of biochar-compost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Previous studies by Tsegaye (2019) examined the effect of different rates of compost application on the growth of carrots, with the results indicating that increasing the compost application rate from 0-75 t/ha nearly tripled the vegetative growth of carrots. Izilan et al (2022) conducted a similar study on Choy Sum and found that increasing the biochar compost application rate increased the biomass of Choy Sum. Aji et al (2021) reported similar results in which the biomass of dwarf crape jasmine increased when the amount of applied compost was increased from 0-20%.…”
Section: Yield Production Of B Rapa With Compostmentioning
confidence: 99%
“…Previous studies by Tsegaye (2019) examined the effect of different rates of compost application on the growth of carrots, with the results indicating that increasing the compost application rate from 0-75 t/ha nearly tripled the vegetative growth of carrots. Izilan et al (2022) conducted a similar study on Choy Sum and found that increasing the biochar compost application rate increased the biomass of Choy Sum. Aji et al (2021) reported similar results in which the biomass of dwarf crape jasmine increased when the amount of applied compost was increased from 0-20%.…”
Section: Yield Production Of B Rapa With Compostmentioning
confidence: 99%
“…Right now, using biochar and compost together is seen as a highly effective and sustainable agricultural approach to reduce environmental risks and boost soil fertility and crop yields [4,5]. Recent research suggests that biochar is most beneficial in enhancing soil qualities *Corresponding author: endriani@unja.ac.id when it is used alongside or processed together with other soil amendments like biosolids, paper mill sludge, manure, and compost [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This material is a promisor for improving soil physical and hydraulic qualities such as soil structure, water retention, water available content, porosity, infiltration rate, bulk density, and hydraulic conductivity (de Jesus Duarte et al 2019;de Jesus Duarte et al 2020;Laird et al 2010, Herath et al 2013and Abrol et al 2016. Recent studies had proved that the incorporation of biochar with other organic amendments can maximize the potential benefits of soil properties (Izilan et al 2022). Compost is one of the best choices to be combined with biochar because of its positive effects on soil chemical, physical-hydric, and biological contributions (Agegnehu et al 2016;Jaafar et al 2014;Pandit et al 2020;de Jesus Duarte et al 2019).…”
Section: Introductionmentioning
confidence: 99%